Evaluating the optical properties of TiO2 nanofluid for a direct absorption solar collector - Said, Z.; Sajid, M.H.; Saidur, R.; Mahdiraji, G.A.; Rahim, N.A. (Taylor & Francis, 2015)
Recent studies specify that designated nanofluids may increase the proficiency of direct absorption solar thermal collectors. To determine the efficiency of nanofluids in solar applications, their capability to change light energy to thermal energy must be identified (i.e., the absorption spectrum of the solar material). In view of that, this study compares model predictions to spectroscopic measurements of extinction coefficients over wavelengths that are important for solar energy (200- 1100nm). In the first decade of nanofluid research, most of the focus was on measuring and modeling the fundamental thermophysical properties of nanofluids (i.e., thermal conductivity, density, viscosity, and convection coefficients). Lately, considerable focus is given to the fundamental optical properties of nanofluids. However, the effect of particle size, shape, and volume fraction of nanoparticles as well as alternation of the base fluids, which can significantly affect scattering and absorption, have not been addressed to date in the literature. In this study, the effects of size and concentration of TiO2 nanoparticles on the extinction coefficient were analyzed using the Rayleigh approach. The results show that smaller particle size (<20nm) has a nominal effect on the optical properties of nanofluids. Volume fraction is linearly proportionate to the extinction coefficient. Considering a nanoparticle size of 20nm, almost 0 transmissivity is obtained for wavelengths ranging from 200 to 300nm. However, a sudden increase of 71 in transmissivity is noted from 400nm, gradually increasing to 88 and becoming similar to that of water at 900nm. Promising results are observed for volume fractions below 0.1.